2007
DOI: 10.1093/jjco/hym121
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Carbonic Anhydrase IX and Ki-67 Expression in Squamous Cell Carcinoma of the Tongue

Abstract: The expression of CA IX and Ki-67 may be useful for predicting prognosis in squamous cell carcinoma of the tongue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 23 publications
6
54
0
Order By: Relevance
“…Ki-67 expression did not correlate with overall survival in any other stage, possibly because Ki-67 expression below 33% was generally observed in only stage I OTSCC. Other studies in oral cancer investigating the correlation between Ki-67 expression and overall survival in patients found conflicting results although several studies confirmed that a lower Ki-67 expression exhibited better patient survival (Gonzalez-Moles et al, 1996;Piffko et al, 1996;Stoll et al, 2000;Myoung et al, 2006;Kim et al, 2007). One study by Kim et al (2007) observed a significantly longer patient survival when Ki-67 expression was below 10% in OTSCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ki-67 expression did not correlate with overall survival in any other stage, possibly because Ki-67 expression below 33% was generally observed in only stage I OTSCC. Other studies in oral cancer investigating the correlation between Ki-67 expression and overall survival in patients found conflicting results although several studies confirmed that a lower Ki-67 expression exhibited better patient survival (Gonzalez-Moles et al, 1996;Piffko et al, 1996;Stoll et al, 2000;Myoung et al, 2006;Kim et al, 2007). One study by Kim et al (2007) observed a significantly longer patient survival when Ki-67 expression was below 10% in OTSCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study was limited by our small population size; however, OTSCC is a sub-site specific cancer with very few published articles. Methodologically, different approaches in Ki-67 immunohistochemical evaluation were used, making comparison difficult due to lack of one standardised assessment method (Pich et al, 2004;Kim et al, 2007). In addition, a limitation of the study is the heterogeneity of treatment modalities among the different stages of OTSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bettendorf et al (14) concluded that Ki-67 staining alone cannot be used to predict prognosis in patients with oral cancer. Kim et al (17) reported that presence of the Ki-67 bio-marker determines the worst prognosis for patients with OSCC. About 93% of our samples did not stain for the bcl-2 marker and only 6.7% expressed bcl-2 weakly.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B1 is useful in predicting occult cervical lymph-node metastasis in OSCC (Harada et al, 2006). Ki-67 and PCNA are wellestablished cell proliferation markers, and Ki-67 expression increases sharply in early OSCC, but significantly decreases during disease progression (Derka et al, 2006), while that of PCNA was not significantly associated with the survival (Kim et al, 2007;Lim et al, 2005;Myoung et al, 2006). Akt plays a pivotal role in cell survival and proliferation.…”
Section: Cell Cycle Progression and Proliferation Biomarkersmentioning
confidence: 99%